Observation of Eunotia enigmatica (Bacillariophyta), a rare South-American diatom species, in the Congo Basin, tropical Africa. Issue 2 (3rd April 2019) - Cocquyt, Christine; Mambweni Makaya, Jacob; Ngendja Kabitoma, Mamie
ABSTRACT: In material collected in the Losambila river, a small tributary of the Congo River at Yangambi (Tshopo Province, Democratic Republic of the Congo), an unusual Eunotia species was observed. The same taxon was also detected in material taken at the beginning of 2018 in a small tributary of the Luapula river in the Haut-Katanga Province in the South of DR Congo. We could identify it as Eunotia enigmatica, recently described from reservoirs in south-eastern Brazil. The valve morphology of the Congolese material is compared with the Brazilian. E. enigmatica was not observed frequently but was not rare either. In two samples of the Losambila river this taxon reached up to 5.6 and 5.4 % of the total diatom assemblage. It is not the only species with a distribution known from Africa and South-America observed in the Losambila River. Encyonopsis frequenti s, also described from South America, was more common than E. enigmatica in samples collected in the Tshopo Province, and reached up to 16.8% of the total diatom composition in the Losambila river. However, Encyonopsis frequenti s was not observed in the samples where E. enigmatica was present. The same applies to the material from the tributary of the Luapula river where Encyonopsis frequenti s was not found in the sample where E. enigmatica was present.